Phylogeography and demographic history of the Chagas disease vector Rhodnius nasutus (Hemiptera: Reduviidae) in the Brazilian Caatinga biome - Peretolchina, Tatiana; Pavan, Márcio G.; Corrêa-Antônio, Jessica; Gurgel-Gonçalves, Rodrigo; Lima, Marli M.; Monteiro, Fernando A. (PLOS Neglected Tropical Diseases, 2018)
Background Rhodnius nasutus, a vector of the etiological agent Trypanosoma cruzi, is one of the epidemiologically most relevant triatomine species of the Brazilian Caatinga, where it often colonizes rural peridomestic structures such as chicken coops and occasionally invades houses. Historical colonization and determination of its genetic diversity and population structure may provide new information towards the improvement of vector control in the region. In this paper we present thoughtful analyses considering the phylogeography and demographic history of R. nasutus in the Caatinga. Methodology/Principal findings A total of 157 R. nasutus specimens were collected from Copernicia prunifera palm trees in eight geographic localities within the Brazilian Caatinga biome, sequenced for 595-bp fragment of the mitochondrial cytochrome b gene (cyt b) and genotyped for eight microsatellite loci. Sixteen haplotypes were detected in the cyt b sequences, two of which were shared among different localities. Molecular diversity indices exhibited low diversity levels and a haplotype network revealed low divergence among R. nasutus sequences, with two central haplotypes shared by five of the eight populations analyzed. The demographic model that better represented R. nasutus population dynamics was the exponential growth model. Results of the microsatellite data analyses indicated that the entire population is comprised of four highly differentiated groups, with no obvious contemporary geographic barriers that could explain the population substructure detected. A complex pattern of migration was observed, in which a western Caatinga population seems to be the source of emigrants to the eastern populations. Conclusions/Significance R. nasutus that inhabit C. prunifera palms do not comprise a species complex. The species went through a population expansion at 12–10 ka, during the Holocene, which coincides with end of the largest dry season in South America. It colonized the Caatinga in a process that occurred from west to east in the region. R. nasutus is presently facing an important ecological impact caused by the continuous deforestation of C. prunifera palms in northeast Brazil. We hypothesize that this ecological disturbance might contribute to an increase in the events of invasion and colonization of human habitations.